Effects of tillage methods on soil physical properties and crop yield in arid area of northwest China - Li, Juan; Guo, Zhen; Wang, Jiawei (Bangladesh Journal of Botany, 2021)
Effects of no-tillage, deep tillage and tillage on soil physical properties and maize yield in Weibei dryland were studied through field experiments from 2008 to 2010. The results showed that the soil bulk density was the highest under no-tillage treatment. The maximum field water holding capacity and saturated water content were both the highest under deep-plowing treatment, which were 29.66 and 31.31%, respectively. Under the condition of balanced fertilization, during the growth period of maize, the average soil water storage of no-tillage and deep-plowing treatment was 44.2 and 34.6 mm higher than that of ploughing treatment. The yield, water use efficiency and net income of deep-plowing treatment with balanced fertilization were the highest among three combinations of tillage. It can be seen that the treatment of deep loosening with balanced fertilization is the best combination of tillage and fertilization in continuous cropping corn field in Weibei Arid Plateau. Bangladesh J. Bot. 50(3): 819-829, 2021 (September) Special